The impact of pearling as a treatment prior to wheat roller milling on the texture and structure of bran-rich breakfast flakes. Issue 1 (June 2015) - De Brier, N.; Gomand, S.V.; Joye, I.J.; Pareyt, B.; Courtin, C.M.; Delcour, J.A.
Abstract: While wheat bran has an interesting nutritional profile, its inclusion in food recipes can lead to poor structure and sensory quality of the final product. Here, we studied how outer bran layers affect textural and structural properties of breakfast cereal flakes (containing 20 or 40% regular, aleurone-enriched or reconstituted bran). Aleurone-enriched bran was obtained by removing the outer bran layers by pearling and thereby enriching the bran obtained by subsequent roller milling in aleurone tissue while reconstituted bran was obtained by reconstituting aleurone-enriched bran with pearlings. Flakes containing aleurone-enriched bran were more crispy and maintained better hardness during soaking in milk, especially for 40% bran-rich breakfast flakes, than their regular bran containing counterparts. Inclusion of 40% reconstituted bran in the recipe deteriorated the texture and microstructure. The present work demonstrates that pearling offers bran material that is very suitable as ingredient for producing breakfast flakes with improved textural properties. Highlights: Pearling offers suitable bran material for producing flakes with improved texture. Flakes of aleurone-enriched bran better maintained hardness during soaking in milk. Flakes of aleurone-enriched bran were more crispy. Reconstituted bran deteriorated texture and microstructure of the flakes.